The zakat as investment of mustahiq |الزكاة كاستثمار للمستحق - Hamzah Hasan (Al-Zahra : Journal for Islamic and Arabic Studies, 2008)
Zakat as one of Islamic principles is not only asdevotion for the muzakki but it is also as investmentfor the mustahiq. As infestation zakat is an instrumentthat generates income. Al-Qur'an states certain kindsof mustahiq, which are not as passive receiver butobliged to struggle for certain values. Thus, theresponsibility of amil zakat is not confined only todistribute the zakat, but also to make it moreproductive and profitable for the mustahiq.